The Convergence of Double-Indexed Weighted Sums of Martingale Differences and Its Application - Wenzhi Yang; Xinghui Wang; Xiaoqin Li; Shuhe Hu (Abstract and Applied Analysis)
We investigate the complete moment convergence of double-indexed weighted sums of martingale differences. Then it is easy to obtain the Marcinkiewicz-Zygmund-type strong law of large numbers of double-indexed weighted sums of martingale differences. Moreover, the convergence of double-indexed weighted sums of martingale differences is presented in mean square. On the other hand, we give the application to study the convergence of the state observers of linear-time-invariant systems and present the convergence with probability one and in mean square.